Postcovid syndrome: regarding the risks of developing thrombotic complications in patients with ischemic limb lesions (clinical cases) - T.P. Nikolaenko-Kamyshova; O.M. Biesiedin (Medičnì Perspektivi, 2021)
The problem of postcovidal syndrome is currently relevant, since in the stabilization of vital functions, the processes of immunological inflammation with significant disorders of endothelium functions continue; this causes tissue ischemization, especially in the presence of changes at the level of microcirculation in patients with angiopathy and vasculopathy. It is noted that in COVID-19 comorbidity with hypertension, coronary heart disease, diabetes mellitus, systemic connective tissue diseases the risks, course, prognosis and development of vascular complications significantly increase. The severity of the inflammatory process and predicting the likelihood of complications is accompanied by changes in laboratory indicators, namely: in the general blood test – leukocytosis, an increase in the level of neitrophilic granulocytes, a decrease in the content of hemoglobin and platelets; in biochemical indicators – a decrease in the level of the general protein, an increase in the indicators of alaninetransferase, aspartaminotransferase, C-reactive protein, lactatdehydrogenase, ferritin; coagulation changes – increase in the level of fibrinogen, D-dimer, reduction of activated partial thromboplastic time. On the basis of the considered clinical cases, taking into account modern ideas about the peculiarities of the development of thrombotic complications in COVID-19 infection in patients with ischemic lesions of the extremities, the need to prescribe low molecular weight heparin  as a selection drug for the treatment of thrombophilic conditions has been proven. Detailed study of histological material is important for establishing changes at the level of microcirculation and ischemization of tissues, this will allow to develop algorithms for the treatment and prevention of complications. Solving these issues, not only in the presence of COVID-19, but also in any stressful cases, requires careful clarification of the mechanisms for the development of complications and a timely adequate integrated approach to treatment to improve and stabilize the condition of patients.